Efektivitas Video Instruksional untuk Meningkatkan Keterampilan Pemecahan Masalah pada Siswa Sekolah Dasar dalam Ilmu Bumi - Zurmanely; Ketang Wiyono; Ermayanti (Postgraduate, University of Mataram, 2025)
This study aimed to develop and examine the effectiveness of an interactive experiment-based instructional video on the topic of the Earth’s rotation and revolution to enhance elementary students’ problem-solving skills. The research employed a Research and Development (R&D) method using the Four-D model (Define, Design, Develop, Disseminate), implemented at SD Negeri Rantau Pangeran, South Sumatra. The research subjects consisted of 30 sixth-grade students. Data were collected through observation, questionnaires, expert validation, and pretest–posttest assessments, then analyzed using the Likert scale and N-gain calculation. The validation results showed an excellent level of feasibility across all aspects: material (91.20%), language (95.20%), and media (91.53%). The practicality test obtained an average score of 98% (individual test) and 94% (small group test), indicating that the media was easy to use and understand. The effectiveness test showed a significant improvement in students’ problem-solving abilities, with the average pretest score increasing from 38.16 to 88.33 on the posttest and an N-gain score of 0.81 (high category). Improvements occurred across all problem-solving indicators, including understanding the problem, planning strategies, executing the plan, and evaluating the results. These findings confirm that the interactive experiment-based instructional video is valid, practical, and effective in stimulating students’ critical thinking and problem-solving skills, making it relevant to the 21st-century competency demands.